Keterbandingan Standar Akuntansi Sewa PSAK 30 Sebelum Dan Setelah Konvergensi IFRS - Armelia Ari Firdatama (AKUNTANSI 45, 2023)
This study aims to analyze the comparability of lease accounting standards, PSAK 30, before the convergence of IFRS (International Finance Reporting Standard) which was carried out in 2008 to 2015. The revision of PSAK 30 is said to have a significant difference between the two revisions, namely the 2007 revision and the 2011 revision. This research was conducted using qualitative methods on the form of literature studies as from documents, articles, journals, and books. The results of the study indicate that there are differences in the treatment of leased assets from the two revisions of PSAK 30, which include grammar, explanation, treatment of economic useful lives, minimum lease payments, and treatment of land and building assets.